Analysis of the genetic diversity of Some rice varieties using microsat-ellite-markers technology - Th. Abdul- Hussain AL-Refeay, Z.; Ab.H. Messan Al–Badeiry2, N. (Journal of Kerbala for Agricultural Sciences, 2018)
genetic diversity of the eleven varieties of Oryza sativa L using molecular indicators collaboration with Mashkhab research center in the Najaf. Use polymerase chain reaction based the indicators Simple Sequence Repeats ,the DNA isolated from fresh leaves rice after 25 days from sowing using Genomic DNA plant kit Protocol . the amount of DNA in good range (125-589) ng/μl purity of 1.8-1.9 . after agarose gel electrophoresis & staining with ethidium bromide. results showed that 64 alleles using 13 primers. The range of molecular size between (1015.402-115.423bp). RM3412 primer reached the highest number of 8 alleles While the lowest number of alleles of 2 alleles recorded RM201,RM10772 primers. The Polymorphism information content (PIC), which is a reflection of the diversity of allelic and repetition allelic between varieties ranged value between (0.0830 -0.8434) . As ranged genetic dimension values ​​between) 0.0868- 0.8595 (. Record all of the primer RM3412 higher values ​​ Heterozygote reached 1. this primers (RM3412 and RM8085) to give a distinctive genetic fingerprinting of three varieties under study. The lowest genetic distance 0.3269 between varieties 2 and 3 this means there is a high degree of similarity. The genetic similarity of all varieties and compositions ranged betwee ) 0.1154 - 0.6731) depend on the genetic distance that ranging from) (0.8846 -0.3269) which refers to the large genetic diversity ranged from(88% -32%) (and this reveals a high genetic variation between varieties making it hereditary rich sources. Results showed of the Cluster analysis to 2 major groups (Main Cluster) at the level of the similarity of 0.12..